(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
The article contains thoughts and opinions about the philosophical-conceptual nature of the fighting spirit of a military serviceman, its place in civilizational paradigms, its components, psychological foundations, and its significance today.